Vitamin K - Zainul Azlan, Nurhazirah; Md Isa, Muhammad Lokman; Ahmad Arifin, Syamsul; Othman, Noratikah; Abd. Rashid, Norlinda; Jainlabdin, Mohd Hanif; Abdul Razak, Redzuan Nul Hakim; Abd. Jalil, Mohd. Azri; Ahmad, Azmir; Tengku Zakaria, Tengku Muhamad Faris Syafiq (2021)
The PBL consists of 2 triggers; Trigger 1 was the description of a patient's complaint and Trigger 2 was the patient's history and physical examination. This PBL aims to expose the student to the possible causes lo uncontolled bleeding and discuss the pathology of blood clotting, risk factors, and complications that arise from inabiJity of blood to clots; and study the pharmacology related to blood clotting.